The Role of Innovation in Small and Medium-Sized Family Firms: A Literature Review - Zizlavsky, Ondrej; Janickova, Nikola (Archives of Business Research, 2021)
This article builds on existing family business research conducted worldwide and embeds the research results in the Czech context to portray the Czech Republic as a critically important context for extending our knowledge on important family firms’ topics. In this article, we present a systematic review and integration of 69 articles published in peer-reviewed journals by Elsevier, Emerald, Wiley and others from 2015 to 2021 in order to answer two research questions: what is the role of innovation in SME family firms and what drives the innovation in family firms? Specifically, the content of the article discusses the new definition of family firm in the Czech Republic; the relationship between innovation and family firm growth; and some contextual factors that might affect the innovations in the Czech SME family firms: ability and willingness paradox, socioemotional wealth, and familiness. The insights of this review are used to develop suggestions for future research in setting the value of family firm where innovation can play an essential role as one of the core value drivers.